Immunogenicity and Safety of an F-Genotype Attenuated Mumps Vaccine in Healthy 8- to 24-Month-Old Children. (1st August 2018) - Liang, Yan; Che, Yanchun; Yang, Beifang; Zhan, Faxian; Li, Hong; Guan, Xuhua; Zhang, Ying; Yin, Qiongzhou; Li, Changgui; Li, Jing; Zhao, Zhimei; Liu, Longding; et al.
Abstract: Background: Mumps vaccine immunizations have reduced the incidence of this disease. With the variation of mumps circulating strain, novel vaccine strains are always important. Methods: A 2-center parallel, randomized, double-blind noninferiority trial was performed to compare an F-genotype attenuated mumps vaccine (SP strain) to the A-genotype vaccine (S-79, Jeryl-Lynn strain) in 1080 healthy children aged 8–24 months in Hubei, China. Results: Participants were randomly assigned to receive a high or low dose of the SP or S79 vaccine and then assessed clinically at 30 minutes and 1–28 days postinoculation. No differences in local or systemic reactivity were observed. A similar incidence of severe adverse events associated with the vaccine was observed in the high-dose group and the positive control group. Based on throat swab collections, no viral shedding was present at the 4th and 10th days in any group. Neutralizing and hemagglutination-inhibiting antibody assays with the F- or A-genotype strains showed similar trends in geometric mean titers in the high-dose SP and S79 groups. Increased cytotoxic T lymphocyte responses were observed in all groups. Conclusions: The F-genotype attenuated mumps vaccine is safe, offers immunogenicity against a homologous virus, and is noninferior to the A-genotype vaccine in 8- to 24-month-old children. Abstract : The phase II trial of a novel F-genotype attenuated mumps vaccine made with a circulating strain in healthy children 8 to 24 months of age shows safety, good immunogenicity, and noninferiority to the current A-genotype vaccine.